Estratégias e práticas educativas dos negros na comarca do Rio das Velhas, século XVIII - Solange Maria da Silva (2011)
In this study it is made a reading of the strategies and educational practices undertaken and actualized by freed slaves in the county of Rio das Velhas in the eighteenth century. For that, I had as basis the concept of education in a more extended shape than the scholar context, considering the actions practiced by the freed slaves in the spaces of brotherhoods, in the world of crafts and in the private space. These spaces provided exchange of knowledge and techniques and also social and cultural learning that combined, recreated and adapted in the daily contacts between the subjects guided survival strategies, strategies for social inclusion, and strategies of knowledges apprehension. I tried to articulate Historiography of Brazilian Slavery with the History of Education, being aware to pedagogical/educational phenomena and to the experience of the subjects. The research was developed through wills and inventories, using theoretical approach of the New Social History. In this way, the study shows the singularities of the educational practices and social experiences from the freed slaves, allows focusing on these singularities and allows comprehending better the process of knowledge and of the literate way involving this ethnic group in eighteenth century in Minas Gerais.